1995
DOI: 10.1002/cber.19951280713
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Route to Halogenated Arsaborane Clusters: Crystal Structure of 3,4,5,6‐Tetrachloro‐1,2‐diarsa‐closo‐hexaborane(4)

Abstract: Copyrolysis of BzC14 and AsC1, at 330 "C leads to the forma-the products. At temperatures above 400 "C and higher tion of closo-1,2-As2B4C14 (1) and further products the mass B2C14/AsC13 ratios the formation of AszBloCllo is preferred to spectral evidence of which suggests that they are perchlorithat of smaller arsaboranes. A single-crystal X-ray study of 1 nated arsaboranes AsZB5Cl5, As4B8C16, and AszBloCllo. The confirmed that, consistent with its 14-skeletal electron count, pyrolysis temperature and the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 11 publications
1
17
0
3
Order By: Relevance
“…Since each signal exhibits more than one cross peak, this allows only the 1,2‐conformation. Consistent with the assignments previously made for 1,2‐As 2 B 10 Cl 10 ,[3b] 2 contains boron atoms B4,5,7,11 and B8,10 that are directly linked to all other boron sites. Thus, the signal with a relative intensity of four at 0.6 ppm is assigned to B4,5,7,11 and the signal at δ = –1.6 ppm to B8,10.…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…Since each signal exhibits more than one cross peak, this allows only the 1,2‐conformation. Consistent with the assignments previously made for 1,2‐As 2 B 10 Cl 10 ,[3b] 2 contains boron atoms B4,5,7,11 and B8,10 that are directly linked to all other boron sites. Thus, the signal with a relative intensity of four at 0.6 ppm is assigned to B4,5,7,11 and the signal at δ = –1.6 ppm to B8,10.…”
Section: Resultsmentioning
confidence: 85%
“…The previous study of the co‐pyrolysis of B 2 Cl 4 with AsCl 3 at 330 °C was found to only produce the polyhedral arsaborane closo ‐1,2‐As 2 B 4 Cl 4 . [3a] However, when the thermolysis reaction was carried out using more severe conditions (450 °C), production of the arsaboranes closo ‐1,2‐As 2 B 10 Cl 10 and conjuncto ‐(As 2 B 4 Cl 3 ) 2 was also observed. [3b]…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations